Health conditions and occupational risks in a novel group: waste pickers in the largest open garbage dump in Latin America - Vanessa Resende Nogueira Cruvinel; Carla Pintas Marques; Vanessa Cardoso; Maria Rita Carvalho Garbi Novaes; Wildo Navegantes Araújo; Antonia Angulo-Tuesta; Patrícia Maria Fonseca Escalda; Dayani Galato; Petruza Brito; Everton Nunes da Silva (BMC Public Health, 2019)
Abstract Background The inadequate management of solid waste impacts populations’ health and quality of life, and disproportionately affects developing countries. This study aims to describe a protocol for epidemiological diagnosis, the purpose being to estimate the prevalence of chronic and communicable and non communicable diseases in waste pickers, and the occupational and environmental risk factors to which these are exposed. Methods This is a cross-sectional study, based on survey design in an area of extreme social vulnerability – the largest garbage dump in Latin America. Using a multidimensional research protocol, divided in three stages: 1- The identification of the subjects, and the scheduling of tests; 2- Situational diagnosis through interviews, anthropometric evaluation, measuring blood pressure, collecting hair and nail samples to detect exposure to heavy metals and undertaking laboratory tests; 3- The return of the waste pickers to receive the test results, followed by referral to the health team and to report occupational accidents. Results One thousand twenty-five waste pickers undertook tests and interviews. The majority were women (67.0%), with 36–45 years old (45.7%), and 96.0% had children. In total, 27.3% of the participants did not attend to any school and 47.7% were educated only up to primary level. The majority of waste pickers (68.70%) reported accidents and most of them (89.69%) were related to sharp objects. The mean time working in this open dump was 15 years. According the anthropometric measure, 32.6% were overweight and 21.1% were obese. The most common reported diseases were: osteomuscular disorders (78.7%); arboviruses (28.6%); episodic diarrhea (24.9%); hypertension (24.2%); bronchitis (14.3%); intestinal worms (12.6%) and diabetes (10.1%). According to the blood tests, the values outside the reference limits were: Uric acid (23.89%); creatinine (54.06%); GGT range (16.04%); SGOT - Serum Glutamic Oxaloacetic Transaminase (5.29%); SGPT - serum Glutamic-Pyruvic Transaminase (35.52%). Conclusions This study is the first to evaluate multiple risks and diseases in the majority of waste pickers working in the largest garbage dump of a continent. These findings highlight the importance to address urgently the environmental, social and health impacts related to the management of solid waste in developmental countries to protect these workers and their families.